Permian–Triassic adakitic igneous activity at Northern Mongolia: Implication for Permian–Triassic subduction system at the Siberian continental margin. (May 2022) - Umeda, Kanta; Purevsuren, Nemekhbayar; Tsukada, Kazuhiro; Altansukh, Lodoidanzan; Nadmid, Bayart; Sodnom, Khishigsuren; Nuramkhaan, Manchuk; Kabashima, Taro; Kondo, Tomoyuki
Abstract: The geochemistry of the Permian–Triassic large-scale igneous rock body of northern Mongolia is a key factor in understanding the subduction-related magmatism at the margin of "Siberian continent." Several studies have been done in the Permian–Triassic igneous body; however, its detailed magmagenesis and tectonic significance remain unclear. This paper investigates the geochemistry of the Upper Permian andesites (Bugat/Baruunburen Formation) and the Late Permian–Middle Triassic plutonic rocks (Selenge plutonic rock complex) of the Permian–Triassic igneous body, and intermediate dike intruding into them, and discusses the Late Permian–Middle Triassic magmatism of the Siberian continental margin. These rocks show a linear distribution on the variation diagram. They are therefore likely to be derived from a single magmatic source. The rocks, characterized by low K2 O/Na2 O, high Sr/Y, high La/Yb, and high Sr/La ratios are adakitic rocks of basaltic slab-melt origin. The samples are enriched in Cr and Ni and have a high Mg# compared with the typical slab-melt. This is likely due to an interaction between the slab-melt and the overlying mantle peridotite during its ascent. The Nb/Ta variation of the samples may point crustal contamination to the magma. The paleolatitude of the Bugat/Baruunburen Formation is calculated to be 37.1° N based on thermal remanent magnetization. Therefore, the Late Permian–Middle Triassic large-scale adakitic igneous activity had taken place in the volcanic arc along the Siberian continental margin in the mid-latitudes of the Northern Hemisphere. The geochemical characteristics of the intermediate dike are almost the same as those of the Bugat/Baruunburen Formation and the Selenge plutonic rock complex, indicating that adakitic igneous activity continued after the Early Triassic. Graphical Abstract: ga1 Highlights: The Permian–Triassic igneous rocks at the Siberian continental margin are adakitic rocks of old/cold slab-melt origin. The high Mg# of the samples indicates an interaction between the slab-melt and the overlying mantle peridotite. The slab-melting likely caused by flat subduction, oblique subduction, or heat supply from superplume of Siberian traps. Geochemical features of the intermediate dike suggest that the adakitic magmatism lasted till after the Early Triassic.